Estudio Exploratorio sobre la Utilización de Técnicas de Análisis de Regresión y de Análisis Conjunto en los Estudios del Comportamiento del Consumidor - Gouvêa, Maria Aparecida; Prearo, Leandro Campi; Romeiro, Maria do Carmo (Review of Business Management, 2010)
This paper is part of a large study to assess the adequacy of the use of multivariate statistical techniques in theses and dissertations of some higher education institutions in the area of marketing with theme of consumer behavior from 1997 to 2006. The regression and conjoint analysis are focused on in this paper, two techniques with great potential of use in marketing studies. The objective of this study was to analyze whether the employment of these techniques suits the needs of the research problem presented in as well as to evaluate the level of success in meeting their premisses. Overall, the results suggest the need for more involvement of researchers in the verification of all the theoretical precepts of application of the techniques classified in the category of investigation of dependence among variables. Key words: Quantitative methods. Analysis of multiple regression. Analysis joint. Consumer behavior.